2011
DOI: 10.3758/s13414-011-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

Refining the dual-stage account of intertrial feature priming: Does motor response or response feature matter?

Abstract: Numerous studies have shown that repetition of search-relevant attributes facilitates visual search performance. For example, Maljkovic and Nakayama (1994) showed that when observers search for a target defined by its color and report its shape, repetition of the target color speeds search, an effect known as priming of pop-out. While intertrial feature priming in search was initially thought to affect perceptual processes, the idea that it also affects postselection stages of processing is increasingly acknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…Recent work from our lab however, has shown that the number of trials over which PoP can be measured is strongly affected by contextual reinstatement that is both perceptual (Thomson & Milliken, 2012) and nonperceptual (Thomson & Milliken, in press) in nature, suggesting that retrieval interference may at least partially dictate the magnitude of PoP effects. In addition, recent theoretical accounts of PoP have been forwarded that acknowledge a role for both feed-forward mechanisms, as well as episodic retrieval contributions to the PoP effect (Lamy, Yashar, & Ruderman, 2010;Yashar & Lamy, 2011). As a result, the attentional control over the magnitude of PoP shown in the present work could result from either control over feature weights from one trial to the next or control over event integration, if indeed both such processes contribute to PoP effects.…”
Section: Discussionmentioning
confidence: 78%
“…Recent work from our lab however, has shown that the number of trials over which PoP can be measured is strongly affected by contextual reinstatement that is both perceptual (Thomson & Milliken, 2012) and nonperceptual (Thomson & Milliken, in press) in nature, suggesting that retrieval interference may at least partially dictate the magnitude of PoP effects. In addition, recent theoretical accounts of PoP have been forwarded that acknowledge a role for both feed-forward mechanisms, as well as episodic retrieval contributions to the PoP effect (Lamy, Yashar, & Ruderman, 2010;Yashar & Lamy, 2011). As a result, the attentional control over the magnitude of PoP shown in the present work could result from either control over feature weights from one trial to the next or control over event integration, if indeed both such processes contribute to PoP effects.…”
Section: Discussionmentioning
confidence: 78%
“…In line with the response biasing account, reaction times are often faster when both the target and response repeat than when only either the target or the response repeats (e.g., Hillstrom, 2000;Huang & Pashler, 2005;Meeter & Olivers, 2006;Müller & Krummenacher, 2006;Töllner et al, 2008;Yashar & Lamy, 2011). Yet, at least with respect to feature changes, changing the response requirements do not completely eliminate target switch costs, indicating that they cannot be fully accounted for by response biasing (e.g., Hillstrom, 2000;Yashar & Lamy, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…For example, in a target present/absent search task, changing the target dimension (e.g., from a color to a size target) would automatically create a bias to change the response as well, which would lead to switch costs when the target changes but the instructed response is the same as on the previous trial (e.g., a target present response; Becker, 2008aBecker, , 2010aCohen & Magen, 1999;Mortier, Theeuwes & Starreveld, 2005;Pollmann et al, 2006;Yashar & Lamy, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations